Gestão de documentos, gestão de documentos da informação e do conhecimento e fluxos informacionais: estudo de caso da panificadora Bom Jesus - SANTOS, Júlio Eduardo Ferreira dos (2023)
Informational flows are dynamic processes capable of highlighting advantages and disadvantages within an organization to allow better decision-making. With this concept, the research follows the following question: what are the contributions of document management, information management and knowledge management, for the identification of informational flows within the scope of enterprises? As a sample cut, a case study was carried out at “Padaria Bom Jesus”, located in Belém do Pará. In this way, it was also possible to understand how the informational flows occur in that enterprise. The study was based on the bibliographical survey, in this way, qualitative research was carried out through the application of semi-structured interviews, to the employees of the enterprise in question. This study made it possible to get to know the establishment to identify and understand the document management and informational flows of the place. With this, it was possible to highlight some of the needs related to document management, information management and knowledge management, such as administrative and operational failures.